2015
DOI: 10.2147/ott.s92361
|View full text |Cite
|
Sign up to set email alerts
|

The XRCC1 Arg194Trp polymorphism is significantly associated with lung adenocarcinoma: a case-control study in an Eastern European Caucasian group

Abstract: DNA repair plays an important role in maintaining the integrity of the genome by repairing DNA damage induced by carcinogens. Certain genetic polymorphisms that occur in DNA-repair genes may affect the ability to repair DNA defects, and may represent a risk factor in carcinogenesis. The gene XRCC1 is involved in DNA repair. The purpose of our study was to investigate the association between XRCC1 Arg194Trp and Arg399Gln polymorphisms and the risk of lung cancer in a Romanian population. We recruited 222 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…So far, several studies have reported on the association between XRCC1 polymorphisms and development of several types of cancers, including non-small cell lung cancer, gastric cancer, cervical cancer, hepatocellular carcinoma, pancreatic cancer, ovarian cancer, colorectal cancer, and thyroid cancer (Liu et al, 2012;Abdel-Fatah et al, 2013;Feng et al, 2014;Wang and Ai, 2014;Xia et al, 2014;Cătană et al, 2015;Han et al, 2015;Huang et al, 2015;Xu et al, 2015;Zhao and Chen, 2015;Ghosh et al, 2016). Liu et al (2015) observed a significant relationship between the XRCC1 Arg399Gln polymorphism and risk of cervical cancer in a meta-analysis comprising 2051 cervical cancer patients and 2919 control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies have reported on the association between XRCC1 polymorphisms and development of several types of cancers, including non-small cell lung cancer, gastric cancer, cervical cancer, hepatocellular carcinoma, pancreatic cancer, ovarian cancer, colorectal cancer, and thyroid cancer (Liu et al, 2012;Abdel-Fatah et al, 2013;Feng et al, 2014;Wang and Ai, 2014;Xia et al, 2014;Cătană et al, 2015;Han et al, 2015;Huang et al, 2015;Xu et al, 2015;Zhao and Chen, 2015;Ghosh et al, 2016). Liu et al (2015) observed a significant relationship between the XRCC1 Arg399Gln polymorphism and risk of cervical cancer in a meta-analysis comprising 2051 cervical cancer patients and 2919 control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that XRCC1 Arg194Trp polymorphism was an independent risk factor in female patients with lung adenocarcinoma. 27 Our study patients with lung adenocarcinoma were chosen on the basis of the described previously reasons. We found rs3769821 of CASP8 is an independent prognostic factor associated with OS of the lung adenocarcinoma in our study patients.…”
Section: Immortality Of Injured Cells and Induction Of Various Cancersmentioning
confidence: 99%